English Language Learners and Judicial Oversight: Progeny of Castañeda - Lenford C. Sutton; Luke Cornelius; Robyn McDonald-Gordon (Educational Considerations, 2012)
When the 93rd Congress enacted the Equal Education Opportunity Act of 1974 (EEOA), it required states to take appropriate action to overcome language barriers that inhibited equal education participation by their resident students.
Keywords: education; opportunity; English Language Learners; Judicial; U.S. Supreme Court; policy; implications; immigration; reforms